KEWENANGAN BADAN PERMUSYAWARATAN DESA (BPD) DALAM MELAKSANAKAN FUNGSI LEGISLASI PADA PROSES PENYUSUNAN PERATURAN DESA : Studi di Desa Sikayu, Kecamatan Buayan, Kabupaten Kebumen, Provinsi Jawa Tengah - Rostania Nur Asiyah (2022)
As stated in article 55 of Law Number 6 of 2014 concerning Villages, that the Village Consultative Body in this case has a function, one of which is to discuss and agree on the Draft Village Regulation with the Village Head or it can be called a legislative function. This study aims to determine and examine the authority of the BPD in Sikayu Village, Buayan District, Kebumen Regency. In particular regarding the practice of forming Village Regulations, related to the realization of the legislative function of the BPD, whether it is in accordance with the normative provisions of the applicable laws and regulations, and what obstacles are faced by the BPD in the formation of Village Regulations. With the empirical juridical method, this research is studied through the approach of statutory regulations (statutes approach) and traced throughlibrary researchand stakeholder interviews in Sikayu Village. This research results that the suitability of the role of the BPD in the realization of the legislative function does not go hand in hand with the practice of forming Village Regulations. The research process carried out showed that the low level of education possessed by representatives from each hamlet was the most fundamental obstacle, and the practice of forming village regulations was exacerbated by the lack of socialization of village officials with the Sikayu Village BPD before the practice of forming village regulations was implemented.